2014
DOI: 10.1586/1744666x.2015.983081
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects and therapeutic role of C5a in cancer

Abstract: The specific role of C5a in cancer, especially in melanoma, has yet to be determined. Differential effects of C5a could be cancer-specific. In the host defense system, C5a functions to protect the body from harmful entities via a plethora of mechanisms. Yet, C5a may also serve to potentiate cancerous process. C5a facilitates cellular proliferation and regeneration by attracting myeloid-derived suppressor cells and supporting tumor promotion. In this article, we critically reviewed the properties, mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…In the immune system, complement is involved in several mechanisms, but recently one of its components, C5a may also serve to potentiate cancerous process. C5a is known as a potent chemoattractant, hence it facilitates cellular proliferation and regeneration by attracting MDSCs and supporting tumor promotion 28 . For the first time, in 2012 it was shown that C5a, plays an inhibitory role for conventional dendritic cells (DCsc)-mediated NK-cell activation.…”
Section: Cells That Sustain the Inflammatory Milieumentioning
confidence: 99%
“…In the immune system, complement is involved in several mechanisms, but recently one of its components, C5a may also serve to potentiate cancerous process. C5a is known as a potent chemoattractant, hence it facilitates cellular proliferation and regeneration by attracting MDSCs and supporting tumor promotion 28 . For the first time, in 2012 it was shown that C5a, plays an inhibitory role for conventional dendritic cells (DCsc)-mediated NK-cell activation.…”
Section: Cells That Sustain the Inflammatory Milieumentioning
confidence: 99%
“…The CCL2 promotes lung metastasis of breast cancer cells . Furthermore, complement C5 functions to strongly attract cancer cells …”
Section: Resultsmentioning
confidence: 99%
“…17 Furthermore, complement C5 functions to strongly attract cancer cells. 18 Among these chemokines, Eisenblaetter et al recently reported an unusual role of Ccl2 in S100A8/A9-mediated breast cancer metastasis to the lung. 7 They succeeded in vivo imaging of S100A8/A9 using its antibody-based SPECT and revealed that Ccl2 mediates tumor metastatic niche formation in the lung before cancer cells migrate to the lung.…”
Section: Evaluation Of the Decoysmentioning
confidence: 99%
“…The chemotaxis receptor function of myeloid cell–expressed C5aR1 (in response to C5a ligation) in costimulatory blockade‐induced allograft survival has not been previously reported, but C5aR1 signaling has been linked to chemotaxis functions, and several groups have shown that C5a/C5aR1 ligations on tumor‐associated MDSCs facilitate MDSC accumulation into the tumor, promote angiogenesis, and prevent T cell–mediated tumor rejection by augmenting Tregs and inhibiting Teffs . The observations that C5aR1 is required for Mreg migration/accumulation into tumors and into transplants and, as a consequence, to mediate tumor and transplant survival illustrate commonality of mechanism despite distinct pathophysiologic contexts.…”
Section: Discussionmentioning
confidence: 99%